Study of Arsenic-Containing Borates Based on Transformation Products of Industrial Waste - Lekishvili, N.; Jioshvili, G.; Barbakadze, Kh.; Turiashvili, L.; Giorgadze, K.; Rusia, M.; Lomtatidze, Z. (Asian Journal of Chemistry, 2013)
The novel arsenic-containing borates have been synthesized and studied. The composition and structure of the synthesized compounds have been established by physico-chemical analysis, IR, NMR and Mass spectral studies. Preliminary virtual (theoretical) bioscreening of synthesized compounds have been carried out. Biocide properties of obtained compounds were also determined.